Raw material for basalt fiber production produced by mixing quartz rock and basalt and preparation method of raw material
Through the mixed ratio and preparation process of Ying'anite and basalt, the problems of scarce raw material resources and unstable quality in basalt fiber production are solved, and the preparation of high-quality basalt fiber raw materials with low energy consumption and low cost are achieved, and the mechanical of the fiber is improved. Performance and aging resistance.
Patent Information
- Application Number
- CN202411618998.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
In the production of existing basalt fibers, the components of the raw materials are strictly required, resulting in scarce resources, unstable quality, high energy consumption, high production costs, and the process performance cannot meet the new requirements.
Using the mixed ratio of Ying'anite and basalt, raw materials for basalt fiber production are prepared through jaw crushing, ball milling, magnetic separation and reinforced toughening materials, so as to achieve accurate control of components and mineralization. adjust.
The quality of raw materials is stable, energy consumption and production costs are reduced, and the mechanical properties and aging resistance of basalt fibers are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of basalt, and in particular to a raw material for producing basalt fiber produced by mixing dacite and basalt and a preparation method thereof. Background Art
[0002] Basalt fiber is a high-performance inorganic fiber made by rapidly drawing basalt stone through a leaky plate after melting it at high temperature. It has excellent physical and chemical properties such as temperature resistance, single-filament mechanical strength, elastic modulus, density, creep rupture stress, chemical stability, and corrosion resistance is better than that of ordinary glass fiber. At the same time, it produces less waste in the production process, and the product will not pollute the environment after being discarded, and there is no harm, so it is a veritable green and environmentally friendly material. At present, basalt fiber has been used in many fields such as national defense and military industry, civil construction facilities, building reinforcement, marine engineering, ultra-high voltage power transmission, rail transit vehicles, automobile lightweighting, fire protection, and environmental protection.
[0003] At present, the raw materials for basalt fiber production have the following problems:
[0004] 1. Due to the very strict requirements on the composition of basalt powder in basalt fiber production, the available resources are extremely scarce, and most of the basalt cannot be directly used in the production of basalt fiber.
[0005] 2. Due to the extremely complex environmental changes in the natural formation process of basalt, the ore bodies in the same mining area will show different mineral properties, resulting in unstable quality of basalt powder used to produce basalt fiber, and thus unstable quality of basalt fiber finished products.
[0006] 3. Taking the raw materials from Weixian County, Hebei Province, which are currently commonly used in the industry, as an example, the crystallization temperature of the basalt powder from Weixian County, Hebei Province is 1290°C. The crystallization temperature is high and the energy consumption is high. The production cost per ton is generally more than 10,000 yuan.
[0007] 4. Due to the high operating temperature during the production of basalt fiber, the loss of platinum-rhodium alloy is very large, resulting in an increase in production costs.
[0008] 5. The performance of basalt fiber produced by the current production process cannot meet the new requirements. It is urgent to develop new technologies and processes to improve the strength of basalt fiber to adapt to the technological development of emerging fields. Summary of the invention
[0009] The purpose of the present invention is to propose a raw material for basalt fiber production produced by mixing dacite and basalt and a preparation method thereof, and to use a variety of rock minerals for mixing and proportioning, so as to achieve precise control of the components and adjustment of the mineral properties, thereby achieving stable product quality, lower cost, better quality and better mechanical properties.
[0010] The technical solution of the present invention is achieved in this way:
[0011] The present invention provides a method for preparing raw materials for basalt fiber production by mixing dacite and basalt, comprising the following steps:
[0012] (1) crushing dacite ore and basalt ore into particles by a jaw crusher;
[0013] (2) The two ore particles are fed into the ball mill in proportion through precise measurement for grinding and homogenization;
[0014] (3) Grind the two ores through a dry ball mill to a powder in which all minerals are smaller than 40 mesh and no more than 5% of the particles fall under a 100 mesh sieve;
[0015] (4) Through two magnetic separations, the iron produced during the production process and the ferroferric oxide contained in the mineral are removed;
[0016] (5) The mineral powder is fed into a horizontal mixer, and a reinforcing and toughening material is added thereto for further homogenization, and the mixture is bagged and packaged to obtain a raw material for basalt fiber production produced by mixing dacite and basalt.
[0017] As a further improvement of the present invention, the mass ratio of the dacite ore to the basalt ore is 2-3:7-8.
[0018] As a further improvement of the present invention, the diameter of the particles is between 10 and 20 mm.
[0019] As a further improvement of the present invention, in the magnetic separation, the intensity of the first magnetic separation is 2500-3000 Gauss, and the intensity of the second magnetic separation is 1000-1500 Gauss.
[0020] As a further improvement of the present invention, the addition amount of the reinforcing and toughening material is 3-5wt% of the total mass, and the preparation method of the reinforcing and toughening material is as follows:
[0021] S1. Preparation of modified nano calcium oxide: adding nano calcium oxide to ethanol, adding a silane coupling agent with an amino group, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano calcium oxide;
[0022] S2. Preparation of modified nano titanium dioxide: adding nano titanium dioxide to ethanol, adding a silane coupling agent with a double bond, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano titanium dioxide;
[0023] S3. Preparation of Janus nanosheets: Alkyl orthosilicate, epoxy silane coupling agent, double bond silane coupling agent, surfactant and toluene are uniformly mixed to obtain an oil phase, acid solution is added dropwise to the oil phase, heated and stirred for reaction, centrifuged, washed, ball-milled and dried to obtain Janus nanosheets;
[0024] S4. Preparation of enhanced toughening material: Add Janus nanosheets to toluene, add modified nano titanium dioxide and initiator, heat and stir to react, centrifuge, wash, add to acetonitrile, add modified nano calcium oxide, stir to react, centrifuge, wash, dry to obtain enhanced toughening material.
[0025] As a further improvement of the present invention, the average particle size of the nano calcium oxide in step S1 is 100-200 nm, the mass ratio of the nano calcium oxide to the silane coupling agent with amino group is 10:2-3, the silane coupling agent with amino group is selected from at least one of KH550, KH602, and KH792, and the temperature of the heating and stirring reaction is 40-50° C., and the time is 2-4 hours.
[0026] As a further improvement of the present invention, the mass ratio of the nano titanium dioxide and the silane coupling agent with double bonds in step S2 is 10:2-3, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, the silane coupling agent with double bonds is selected from at least one of KH570, A151, and A171, and the average particle size of the nano titanium dioxide is 100-200nm.
[0027] As a further improvement of the present invention, the mass ratio of the alkyl orthosilicate, the epoxy silane coupling agent, the silane coupling agent with a double bond, the surfactant, the toluene, and the acid solution in step S3 is 5-6: 0.7-1.1: 1-1.5: 4-7: 50-70: 10-20, the acid solution is a hydrochloric acid or sulfuric acid solution with a pH of 2-3, the epoxy silane coupling agent is KH560, the silane coupling agent with a double bond is selected from at least one of KH570, A151, and A171, the temperature of the heating and stirring reaction is 65-75°C, the time is 7-10h, and the ball milling time is 0.5-1h.
[0028] As a further improvement of the present invention, the mass ratio of the Janus nanosheets, modified nano titanium dioxide, modified nano calcium oxide and initiator in step S4 is 10:3.5-4.5:1.5-2.5:0.01-0.02, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diacyl peroxide and benzoyl peroxide, the temperature of the heating and stirring reaction is 50-60°C, the time is 3-5h, and the stirring reaction time is 6-8h.
[0029] The present invention further protects a raw material for basalt fiber production produced by mixing dacite and basalt obtained by the above preparation method.
[0030] The invention prepares and adds a reinforcing and toughening material. First, a silicon dioxide Jenus nanosheet is prepared, which has a double bond on one side and an epoxy group on the other side, and modified nano titanium dioxide with a double bond and modified nano calcium oxide with an amino group are prepared. One side of the silicon dioxide Jenus nanosheet is coupled with the modified nano titanium dioxide with a double bond through double bond polymerization, and the other side is coupled with the modified nano calcium oxide with an amino group through an amino group and an epoxy group ring-opening reaction, so that a Jenus sheet with nano calcium oxide on one side and nano titanium oxide on the other side is prepared. The Jenus sheet has a good infiltration effect on basalt and dacite, can be evenly dispersed, and avoids the problem of reduced mechanical properties due to the incompatibility of the modified material.
[0031] At the same time, the side with nano-titanium oxide is well compatible with basalt, and improves the fracture toughness of the fiber through stress-induced phase change toughening and other mechanisms, thereby improving the tensile strength of basalt fiber and increasing the mechanical strength of basalt. The side with nano-calcium oxide is better compatible with dacite, thereby improving the fracture toughness and mechanical strength of the fiber. It also improves the bonding force between the two mineral materials, thereby further reducing the crystallization temperature, improving the aging resistance of the material, reducing the production cost of raw materials and improving the quality of raw materials.
[0032] The present invention has the following beneficial effects:
[0033] The present invention adopts a variety of rock minerals for mixing and proportioning, so as to achieve precise control of the components and adjustment of the mineral properties, thereby achieving stable product quality.
[0034] 2. Selecting small crystal particle basalt greatly reduces energy consumption, and the crystallization temperature of the raw material prepared by the present invention reaches below 1240°C;
[0035] 3. Use magnetic separation technology to reduce the content of ferroferric oxide;
[0036] 4. The present invention is the first to use a combination of basalt + non-basalt dacite, successfully carried out basalt fiber drawing, and obtained the raw materials for basalt fiber production. The preparation method is simple, the finished product cost is low, the quality is good, the mechanical properties are better, the tensile strength and tensile elastic modulus are better, and the aging resistance is better. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Nano calcium oxide, with an average particle size of 100-200 nm, was purchased from Beijing Kedaojin Technology Co., Ltd.
[0039] Nano-titanium dioxide, with an average particle size of 100-200 nm, was purchased from Langfang Lanke Chemical Group Co., Ltd.
[0040] Preparation Example 1 Preparation of reinforced and toughened materials
[0041] The following steps are involved:
[0042] S1. Preparation of modified nano calcium oxide: 10 g of nano calcium oxide was added to 200 mL of ethanol, 2 g of silane coupling agent KH792 was added, heated to 40°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified nano calcium oxide;
[0043] S2. Preparation of modified nano-titanium dioxide: 10 g of nano-titanium dioxide was added to 200 mL of ethanol, 2 g of silane coupling agent A171 was added, heated to 40° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;
[0044] S3. Preparation of Janus nanosheets: 5 g of tetraethyl orthosilicate, 0.7 g of silane coupling agent KH560, 1 g of silane coupling agent A171, 4 g of Span-85, and 50 g of toluene were mixed evenly to obtain an oil phase, 10 g of acid solution was added dropwise to the oil phase, heated to 65°C, stirred for reaction for 7 h, centrifuged, washed, ball-milled for 0.5 h, and dried to obtain Janus nanosheets;
[0045] The acid solution is a hydrochloric acid solution with a pH of 2;
[0046] S4. Preparation of reinforced and toughened materials: Add 10 g of Janus nanosheets into 200 mL of toluene, add 3.5 g of modified nano titanium dioxide and 0.01 g of dimethyl azobisisobutyrate, heat to 50°C, stir to react for 3 h, centrifuge, wash, add into 200 mL of acetonitrile, add 1.5 g of modified nano calcium oxide, stir to react for 6 h, centrifuge, wash, and dry to obtain a reinforced and toughened material.
[0047] Preparation Example 2 Preparation of reinforced and toughened materials
[0048] The following steps are involved:
[0049] S1. Preparation of modified nano calcium oxide: 10 g of nano calcium oxide was added to 200 mL of ethanol, 3 g of silane coupling agent KH550 was added, the mixture was heated to 50° C., stirred for 4 h, centrifuged, washed, and dried to obtain modified nano calcium oxide;
[0050] S2. Preparation of modified nano-titanium dioxide: 10 g of nano-titanium dioxide was added to 200 mL of ethanol, 3 g of silane coupling agent A151 was added, heated to 50° C., stirred for 4 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;
[0051] S3. Preparation of Janus nanosheets: 6 g of tetraethyl orthosilicate, 1.1 g of silane coupling agent KH560, 1.5 g of silane coupling agent A151, 7 g of Span-85, and 70 g of toluene were mixed evenly to obtain an oil phase, 20 g of acid solution was added dropwise to the oil phase, heated to 75°C, stirred for 10 h, centrifuged, washed, ball-milled for 1 h, and dried to obtain Janus nanosheets;
[0052] The acid solution is a sulfuric acid solution with a pH of 3;
[0053] S4. Preparation of reinforced and toughened materials: Add 10 g of Janus nanosheets into 200 mL of toluene, add 4.5 g of modified nano titanium dioxide and 0.02 g of benzoyl peroxide, heat to 60°C, stir and react for 5 hours, centrifuge, wash, add into 200 mL of acetonitrile, add 2.5 g of modified nano calcium oxide, stir and react for 8 hours, centrifuge, wash, and dry to obtain a reinforced and toughened material.
[0054] Preparation Example 3 Preparation of reinforced and toughened materials
[0055] The following steps are involved:
[0056] S1. Preparation of modified nano calcium oxide: 10 g of nano calcium oxide was added to 200 mL of ethanol, 2.5 g of silane coupling agent KH602 was added, the mixture was heated to 45°C, stirred for 3 h, centrifuged, washed, and dried to obtain modified nano calcium oxide;
[0057] S2. Preparation of modified nano-titanium dioxide: 10 g of nano-titanium dioxide was added to 200 mL of ethanol, 2.5 g of silane coupling agent KH570 was added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;
[0058] S3. Preparation of Janus nanosheets: 5.5 g of tetraethyl orthosilicate, 1 g of silane coupling agent KH560, 1.2 g of silane coupling agent KH570, 5.5 g of Span-85, and 60 g of toluene were mixed evenly to obtain an oil phase, 15 g of acid solution was added dropwise to the oil phase, heated to 70°C, stirred for reaction for 8 h, centrifuged, washed, ball-milled for 1 h, and dried to obtain Janus nanosheets;
[0059] The acid solution is a hydrochloric acid solution with a pH of 2.5;
[0060] S4. Preparation of reinforced and toughened materials: Add 10g of Janus nanosheets into 200mL of toluene, add 4g of modified nano titanium dioxide and 0.015g of azobisisobutyronitrile, heat to 55°C, stir and react for 4h, centrifuge, wash, add into 200mL of acetonitrile, add 2g of modified nano calcium oxide, stir and react for 7h, centrifuge, wash, and dry to obtain a reinforced and toughened material.
[0061] Comparative Preparation Example 1
[0062] Compared with Preparation Example 3, the difference is that no modified nano titanium dioxide is added in step S4.
[0063] The details are as follows:
[0064] S4. Preparation of enhanced and toughened materials: Add 2 g of modified nano-calcium oxide to 10 g of Janus nanosheets in 200 mL of acetonitrile, stir and react for 7 h, centrifuge, wash, and dry to obtain an enhanced and toughened material.
[0065] Comparative Preparation Example 2
[0066] Compared with Preparation Example 3, the difference is that no modified nano calcium oxide is added in step S4.
[0067] The details are as follows:
[0068] S4. Preparation of reinforced and toughened material: Add 10 g of Janus nanosheets into 200 mL of toluene, add 4 g of modified nano-titanium dioxide and 0.015 g of azobisisobutyronitrile, heat to 55°C, stir and react for 4 hours, centrifuge, wash, and dry to obtain a reinforced and toughened material.
[0069] Example 1
[0070] This embodiment provides a method for preparing raw materials for basalt fiber production by mixing dacite and basalt, characterized in that it includes the following steps:
[0071] (1) 20 kg of dacite ore and 80 kg of basalt ore were crushed into particles with a diameter of 10-20 mm by a jaw crusher;
[0072] (2) The two ore particles are fed into the ball mill in proportion through precise measurement for grinding and homogenization;
[0073] (3) Grind the two ores through a dry ball mill to a powder in which all minerals are smaller than 40 mesh and no more than 5% of the particles fall under a 100 mesh sieve;
[0074] (4) removing the iron produced in the production process and the ferroferric oxide in the mineral by two magnetic separations; the intensity of the first magnetic separation is 2500 Gauss and the intensity of the second magnetic separation is 1000 Gauss;
[0075] (5) The mineral powder is fed into a horizontal mixer, and the reinforcing and toughening material prepared in Preparation Example 1 is added in an amount of 3 wt% of the total mass, and further homogenized and bagged to obtain a raw material for basalt fiber production produced by mixing dacite and basalt.
[0076] Example 2
[0077] This embodiment provides a method for preparing raw materials for basalt fiber production by mixing dacite and basalt, characterized in that it includes the following steps:
[0078] (1) 30 kg of dacite ore and 70 kg of basalt ore were crushed into particles with a diameter of 10-20 mm by a jaw crusher;
[0079] (2) The two ore particles are fed into the ball mill in proportion through precise measurement for grinding and homogenization;
[0080] (3) Grind the two ores through a dry ball mill to a powder in which all minerals are smaller than 40 mesh and no more than 5% of the particles fall under a 100 mesh sieve;
[0081] (4) removing the iron produced in the production process and the ferroferric oxide in the mineral by two magnetic separations; the intensity of the first magnetic separation is 3000 Gauss and the intensity of the second magnetic separation is 1500 Gauss;
[0082] (5) The mineral powder is fed into a horizontal mixer, and the reinforcing and toughening material prepared in Preparation Example 2 is added in an amount of 5 wt% of the total mass, and further homogenized and bagged to obtain a raw material for basalt fiber production produced by mixing dacite and basalt.
[0083] Example 3
[0084] This embodiment provides a method for preparing raw materials for basalt fiber production by mixing dacite and basalt, characterized in that it includes the following steps:
[0085] (1) 25 kg of dacite ore and 75 kg of basalt ore were crushed into particles with a diameter of 10-20 mm by a jaw crusher;
[0086] (2) The two ore particles are fed into the ball mill in proportion through precise measurement for grinding and homogenization;
[0087] (3) Grind the two ores through a dry ball mill to a powder in which all minerals are smaller than 40 mesh and no more than 5% of the particles are sieved through a 100 mesh sieve;
[0088] (4) removing the iron produced in the production process and the ferroferric oxide in the mineral by two magnetic separations; the intensity of the first magnetic separation is 2800 Gauss and the intensity of the second magnetic separation is 1200 Gauss;
[0089] (5) The mineral powder is fed into a horizontal mixer, and the reinforcing and toughening material prepared in Preparation Example 3 is added in an amount of 4 wt% of the total mass, and further homogenized and bagged to obtain a raw material for basalt fiber production produced by mixing dacite and basalt.
[0090] Comparative Example 1
[0091] Compared with Example 3, the difference is that the reinforced and toughened material is prepared by Comparative Preparation Example 1.
[0092] Comparative Example 2
[0093] Compared with Example 3, the difference is that the reinforced and toughened material is prepared by Comparative Preparation Example 2.
[0094] Comparative Example 3
[0095] Compared with Example 3, the difference is that no reinforcing and toughening material is added.
[0096] Test Example 1
[0097] The raw materials for basalt fiber production produced by mixing dacite and basalt obtained in Examples 1-3 of the present invention and Comparative Examples 1-3 and similar products on the market were tested for the upper limit temperature of crystallization using a gradient temperature furnace (ASTM C829-8). The results are shown in Table 1.
[0098] Table 1
[0099] Group Crystallization upper limit temperature (℃) Example 1 1237 Example 2 1240 Example 3 1235 Comparative Example 1 1259 Comparative Example 2 1260 Comparative Example 3 1267 Commercially available 1290
[0100] It can be seen from the above table that the raw materials for basalt fiber production produced by mixing andesite and basalt obtained in Examples 1-3 of the present invention have a lower upper limit crystallization temperature. When basalt fiber is prepared by basalt drawing, the temperature must be higher than the crystallization temperature. The crystallization temperature of the products obtained in Examples 1-3 of the present invention is below 1240°C, and the crystallization temperature of similar products on the market is above 1290°C. The higher the temperature, the higher the energy consumption and the loss of the platinum-rhodium alloy drawing leak plate, and the higher the cost.
[0101] Test Example 2
[0102] The raw materials for basalt fiber production produced by mixing dacite and basalt obtained in Examples 1-3 of the present invention and Comparative Examples 1-3 and similar products on the market were heated and melt-drawn to prepare basalt fibers. The drawing speed was 6 m / s. The performance of the prepared basalt fibers was tested according to the test method described in GB / T 20310-2006 "Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength". The results are shown in Table 2.
[0103] Table 2
[0104] Group Tensile strength(MPa) Tensile elastic modulus (GPa) Example 1 4957 115 Example 2 4966 117 Example 3 4970 120 Comparative Example 1 4725 109 Comparative Example 2 4704 107 Comparative Example 3 4479 98 Commercially available 2720 83
[0105] It can be seen from the above table that the raw materials for basalt fiber production produced by mixing dacite and basalt obtained in Examples 1-3 of the present invention have better tensile strength and tensile elastic modulus.
[0106] Test Example 3
[0107] The raw materials for basalt fiber production produced by mixing dacite and basalt obtained in Examples 1-3 of the present invention and Comparative Examples 1-3 and similar products on the market were heated and melted and drawn to prepare basalt fibers, with a drawing speed of 6 m / s, to obtain basalt fibers, and subjected to aging resistance tests. Each basalt fiber was placed in hot air at 85°C for artificial accelerated aging for 100 hours, cooled to room temperature, and subjected to tensile strength tests again according to GB / T 20310-2006. The aging resistance was measured by the retention rate of tensile strength, and the larger the value, the better the aging resistance. The results are shown in Table 3.
[0108] Table 3
[0109] Group Aging resistance (%) Example 1 99.0 Example 2 99.2 Example 3 99.5 Comparative Example 1 96.5 Comparative Example 2 95.7 Comparative Example 3 92.2 Commercially available 85.4
[0110] It can be seen from the above table that the raw materials for basalt fiber production produced by mixing dacite and basalt obtained in Examples 1-3 of the present invention have better aging resistance.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing raw materials for basalt fiber production by mixing dacite and basalt, characterized in that: The following steps are involved: (1) crushing dacite ore and basalt ore into particles by a jaw crusher; (2) The two ore particles are fed into the ball mill in proportion through precise measurement for grinding and homogenization; (3) Grind the two ores through a dry ball mill to a powder in which all minerals are smaller than 40 mesh and no more than 5% of the particles are sieved through a 100 mesh sieve; (4) Through two magnetic separations, the iron produced during the production process and the ferroferric oxide contained in the mineral are removed; (5) The mineral powder is fed into a horizontal mixer, and a reinforcing and toughening material is added thereto for further homogenization, and the mixture is bagged and packaged to obtain a raw material for basalt fiber production produced by mixing dacite and basalt.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the dacite ore to the basalt ore is 2-3:7-8.
3. The preparation method according to claim 1, characterized in that: The diameter of the particles is between 10 and 20 mm.
4. The preparation method according to claim 1, characterized in that: In the magnetic separation, the intensity of the first magnetic separation is 2500-3000 Gauss, and the intensity of the second magnetic separation is 1000-1500 Gauss.
5. The preparation method according to claim 1, characterized in that: The addition amount of the reinforcing and toughening material is 3-5wt% of the total mass. The preparation method of the reinforcing and toughening material is as follows: S1. Preparation of modified nano calcium oxide: adding nano calcium oxide to ethanol, adding a silane coupling agent with an amino group, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano calcium oxide; S2. Preparation of modified nano titanium dioxide: adding nano titanium dioxide to ethanol, adding a silane coupling agent with a double bond, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano titanium dioxide; S3. Preparation of Janus nanosheets: Alkyl orthosilicate, epoxy silane coupling agent, double bond silane coupling agent, surfactant and toluene are uniformly mixed to obtain an oil phase, acid solution is added dropwise to the oil phase, heated and stirred for reaction, centrifuged, washed, ball-milled and dried to obtain Janus nanosheets; S4. Preparation of enhanced toughening material: Add Janus nanosheets to toluene, add modified nano titanium dioxide and initiator, heat and stir to react, centrifuge, wash, add to acetonitrile, add modified nano calcium oxide, stir to react, centrifuge, wash, dry to obtain enhanced toughening material.
6. The preparation method according to claim 5, characterized in that: The average particle size of the nano calcium oxide in step S1 is 100-200 nm, the mass ratio of the nano calcium oxide to the silane coupling agent with amino group is 10:2-3, the silane coupling agent with amino group is selected from at least one of KH550, KH602, and KH792, the temperature of the heating and stirring reaction is 40-50° C., and the time is 2-4 hours.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the nano-titanium dioxide to the silane coupling agent with a double bond in step S2 is 10:2-3, the temperature of the heating and stirring reaction is 40-50° C., the time is 2-4 hours, the silane coupling agent with a double bond is selected from at least one of KH570, A151, and A171, and the average particle size of the nano-titanium dioxide is 100-200 nm.
8. The preparation method according to claim 5, characterized in that: The mass ratio of the alkyl orthosilicate, the silane coupling agent with epoxy group, the silane coupling agent with double bond, the surfactant, toluene and the acid solution in step S3 is 5-6: 0.7-1.1:1-1.5:4-7:50-70:10-20, the acid solution is a hydrochloric acid or sulfuric acid solution with a pH of 2-3, the epoxy silane coupling agent is KH560, the silane coupling agent with a double bond is selected from at least one of KH570, A151, and A171, the temperature of the heating and stirring reaction is 65-75°C, the time is 7-10h, and the ball milling time is 0.5-1h.
9. The preparation method according to claim 5, characterized in that: In step S4, the mass ratio of the Janus nanosheets, modified nano titanium dioxide, modified nano calcium oxide and initiator is 10:3.5-4.5:1.5-2.5:0.01-0.02, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diacyl peroxide and benzoyl peroxide, the temperature of the heating and stirring reaction is 50-60°C, the time is 3-5h, and the stirring reaction time is 6-8h.
10. A raw material for basalt fiber production produced by mixing dacite and basalt, obtained by the preparation method according to any one of claims 1 to 9.